2021
DOI: 10.1088/1742-6596/1898/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Factors Influencing the Trust of Millennial Citizens in E-Government

Abstract: This study aims at identifying the effect of the millennial generation’s perceptions regarding risks, security, and trust in the Internet when utilizing e-government services. A total of 291 data items were collected through online surveys and this information was analysed quantitatively with the SEM method by employing the Smart PLS application. The confidence of this generation in applications is observed to be influenced by software quality and trust in the internet, but not information quality and faith in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The measurement of e-government accuracy and consistency affects trust in transactions (Martati & Suminto, 2021). The security, risk perceptions, and trust in e-government services affect users' intentions as well as users' behavior (Assegaff et al, 2021). Trust in the Internet, Internet access, Internet skills, and trust in the government affect the usage intention for e-government services (Dilhani & Priyashantha, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of e-government accuracy and consistency affects trust in transactions (Martati & Suminto, 2021). The security, risk perceptions, and trust in e-government services affect users' intentions as well as users' behavior (Assegaff et al, 2021). Trust in the Internet, Internet access, Internet skills, and trust in the government affect the usage intention for e-government services (Dilhani & Priyashantha, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Technical and governmental factors positively affect people's trust level in e-government services (Alkateeb & Abdalla, 2021). Trust in e-government services, software quality, security, and risk perceptions affect the users' intention to use and users' behavior (Assegaff et al, 2021). Internet access, trust in government, trust in the Internet, and Internet skills influence the intention of e-government services usage (Dilhani & Priyashantha, 2021).…”
Section: Credibility (Trust) and Intention To Use E-government Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assegaff et al evaluated the factors affecting the trust of millennial citizens in e-government in Jambi, Indonesia. They found that software quality, trust in the internet, reliance on applications influenced the generation behavior (Assegaff et al, 2021).…”
Section: Introductionmentioning
confidence: 99%